Analisis Penerapan Good Corporate Governance (Gcg) Dalam Meningkatkan Kinerja Keuangan Pemerintah Kota Medan - Muhammad Iqbal; Fathia Zuhra Nasution; Gendis Raihan Ardha; Raihani Azzahra Aljuned (Journal of Islamic Economics and Finance, 2024)
This mini-research aims to achieve the goals of an entity, a system of rules known as good corporate governance regulates interactions between various interested parties, or stakeholders. The goal of good corporate governance is to control these interactions, prevent strategic errors in an institution's plans, and ensure that errors can be corrected promptly. The National Committee for Governance Policy (KNKG) develops the principles of Good Corporate Governance which include Transparency, Accountability, Independence, Accountability and Fairness. These principles can help an institution achieve its goals.